ลักษณะประจำพันธุ์กับการประเมินและลายพิมพ์ดีเอ็นเอของพันธุ์ฝ้าย - ทัศณีวรรณ ก้อนจันทร์เทศ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Cotton is a member of the genus Gossypim of the family Malvaceae and is the economic important plant in Thai textile industry. There are many elite cottons that are high yield and more resistant to pets and pathogens. In the future, these cultivars will be registered to protect owners intellectual property. To do that, all trails will be used to distinguish each cultivar. This thesis is carried out in order to investigate any quantitative and qualitative traits as well as DNA fingerprint for cotton cultivar identification. Forty-nine traits were characterized in 15 varieties of native and elite cotton cultivars during 2 planting seasons at the Nakhon Sawan Field Crops Research Center. The results showed that thirty-two important traits used to distringuish each cultivar. Almost are reproductive character and vegetative character. The RAPD-based DNA fingerprint for characterized individual found no unique band for identifying any cultivar. The result suggested that RAPD-based DNA fingerprint may not be suitable for characterizing cotton cultivars. This might be due to a narrow genetic base of elite cotton cultivars.